PENGERTIAN DAN TUJUAN ILMU HUKUM ILMU HUKUM SEBAGAI ILMU NORMATIF DAN EMPIRIS - Okran Erikson Atonis; Diyah Khadijah Blegur; Mordekhay Isty Melandry Pobas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Legal science occupies a unique and complex position in the classification of knowledge disciplines. This article aims to provide a systematic explanation of the definition and objectives of legal science, as well as to elaborate comprehensively on the characteristics of legal science both as a normative and empirical science. Using a literature review methodology, this study examines various perspectives from leading legal scholars regarding the nature of legal science. The findings indicate that legal science has a sui generis character that distinguishes it from other sciences, with a dual approach inherent in it: as a normative science that studies legal norms and as an empirical science that examines the functioning of law in society. As a normative science, legal science is prescriptive in nature, focusing on the validity and applicability of legal norms through rechtsdogmatiek or legal dogmatics. Meanwhile, as an empirical science, legal science is descriptive, studying law as a social phenomenon through sociological, anthropological, and psychological approaches. Legal science has theoretical, practical, and critical objectives that are essential for the development of legal theory, legal practice, and legal reform. The duality of normative and empirical approaches does not contradict each other but rather complements each other in providing a comprehensive understanding of law. This article concludes that a clear and comprehensive understanding of the nature of legal science is crucial for developing appropriate research methodologies and supporting the development of legal science in Indonesia that is responsive to social dynamics and justice needs.